Factors Associated with the Nutritional Status of Children Aged 3 - 5 Years at Hasanuddin Mandai Community Health Center, Mandai District, Maros Regency - Nurbaiti, Nurbaiti (Hasanuddin Medan, 2022)
Nutritional problems are essentially a public health problem, but overcoming them cannot be done with a medical approach and health services alone. The causes of nutritional problems are multifactorial, therefore the approach to overcoming them must involve various related sectors. Based on data from the South Sulawesi Health Service in 2005, there were 14,650 (3.45%) children under five who were malnourished. Meanwhile, in the city of Maros, there were 463 (2.40%) children under five who were malnourished, and in particular at the Hasanuddin Mandai Community Health Center in 2006 there were 35 (10.17%) children aged 3 - 5 years who were malnourished. This study aims to determine the factors related to the nutritional status of children aged 3 - 5 years at the Hasanuddin Mandai Community Health Center, Mandai District, Maros Regency. The research design used in this research is analytical descriptive using the